A CURIOUS CASE OF RECURRENT HYPOGLYCAEMIA IN NEUROFIBROMATOSIS - Min, Liew; Zulkifle, Aina Mardiah; Adam, Noor Lita; Sin, Yong Lit; Karim, Nor Afidah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Neurofibromatosis type 1 (NF-1) is commonly associated with neural tumors such as pheochromocytomas, paragangliomas, and duodenal somatostatinomas. However, its association with insulinoma is extremely rare, with only a few cases reported. CASE A 66-year-old female with longstanding NF-1 presented with a six-month history of recurrent symptomatic hypoglycaemia. She was non-diabetic, lived in a nursing home, and had no history of hypoglycaemic agent use. Her episodes, typically occurring during fasting, were associated with intense hunger and resolved with food intake. Capillary glucose readings ranged from 1.7 to 3.1 mmol/L. She was admitted after being found unconscious with a glucose level of 1.7 mmol/L. Clinical examination revealed multiple dermal neurofibromas and café-au-lait spots. In the ward, paired samples during spontaneous hypoglycaemia (glucose 1.6 mmol/L) showed inappropriately elevated insulin (53.9 pmol/L) and C-peptide (465 pmol/L). After intramuscular glucagon (1 mg), her blood glucose rose from 3.0 to 6.4 mmol/L over 60 minutes. Morning cortisol (450 nmol/L) and IGF-1 (113.5 ng/mL) were normal. β-hydroxybutyrate, IGF-2, and sulphonylurea levels were not tested due to financial limitations. These findings confirmed the presence of endogenous hyperinsulinaemia. A pancreatic CT scan was scheduled to localize the suspected insulinoma but was missed twice. She later re-presented with a seizure, likely secondary to hypoglycaemia, as both brain CT and EEG findings were unremarkable. To better control her hypoglycaemia, diazoxide and a calcium channel blocker were initiated. Imaging was subsequently rescheduled to aid in localizing the insulinoma. CONCLUSION Although rare, insulinoma should be considered in NF-1 patients presenting with recurrent hypoglycaemia. Early recognition and appropriate investigation are crucial to prevent serious complications.